The Relationship of Parenting Style and Perception of Sexuality, Gender and Norm of Reproductive Health among Adolescents - Wulandari, Eka Aprilia; Susanto, Tantut; Nur, Kholid Rosyidi Muhammad (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
Parenting is an interaction between children and parents, including fulfilling physical, psychological needs, and socializing norms in society. The results of the adaptation of parenting styles include sexuality, gender, and norm perception (SGNP) in adolescent reproductive health. This study aims to analyze the relationship between parenting style with SGNP in adolescent reproductive health in Patrang District, Jember Regency. This study was a correlational analytic with a cross-sectional approach conducted among 158 participants with a cluster random samÂpling technique. Data collection used a questionnaire to identify the characteristics of participants, parenting with Parenting Style Dimension Questionnaire (PSDQ), and SGNP in adolescent reproÂducÂtive health with Sexuality, Gender, and Norms Questionnaire. Spearman Rank Correlation as an analysis method was used to answer the objectives of this study. Among 158 participants, 65.8% were authoritative parenting, 20.9% were authoritarian and 13.3% were permissive. Besides, 53.2% of adolescents had positive of SGNP in reproductive health. There is a relationship between parenting style and SGNP in adolescent reproductive health (r = 0.193; p = 0.015). Therefore, a planned intervention is needed such as educating parents and adolescents to be able to apply proper parenting to form positive perceptions.